Characterize different lasers transmission on zinc sulfide coating material /lcYeoh Cheen Shin - 492591 Yeoh, Cheen Shin,ld1987-; Noriah Bidin, supervisor; Fakulti Sains
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2010